An Anonymity Region Construction and Two Fold Location Protection Scheme for Improving Source and Sink Location Privacy in WSN - Jayanthi, R; Mohanraj, M (International Journal of Computer Sciences and Engineering, 2019)
Generally, Wireless Sensor Networks (WSNs) refers to a spatially distributed autonomous network which consists of several sensor nodes. These nodes sense and transport the data to the sink node through adjacent nodes. Contextual privacy is the main challenging issue in WSN. The attacker node gathers information from traffic patterns between source and sink. The protection of source and sink location is very essential to prevent the attacker from gathering information. An all-direction random routing algorithm (ARR) was proposed to protect source-location from attacker node. This algorithm utilized agent nodes to establish a path between sources and sink nodes using only local decisions. ARR is efficiently protecting source location but it exposes direction information of sink. So in this paper, ARR is improved by injecting fake packets and random walk of real packets to hide direction information. Additionally, the anonymity of source and sink location is improved by Two-fold location privacy protection scheme where anonymity is constructed around the source and sink node based on geographic information to hide actual location. In anonymity region, packets are sent from a fake source node and received by fake sink node. The number of fake source and sink is selected based on traffic flow.